Evaluation of mandibular anterior alveolus in different skeletal patterns - Nga Hoang; Gerald Nelson; David Hatcher; Snehlata Oberoi (SpringerOpen, 2016)
Abstract Background The boundaries for orthodontic tooth movement are set by the bony support of the dentition. This study compares the mandibular anterior alveolar housing in individuals with low, average, and high mandibular plane angles before orthodontic treatment and measures alveolar bone loss and root resorption after orthodontic treatment. Methods Pretreatment cone-beam computed tomography (CBCT) images of 75 non-growing individuals, 25 in three groups: low-angle (sella-nasion to mandibular plane ≤28°), average-angle (30°-37°), and high-angle (≥39°), were analyzed. Buccolingual bone thickness was measured at the root apex, mid-root, and alveolar crest of the mandibular right central incisor. Pre- and posttreatment CBCT images of 11 low-angle, 20 average-angle, and 27 high-angle patients were compared to determine changes in the alveolus and mandibular incisor root after orthodontic treatment. Results The pretreatment anterior alveolar bone widths were significantly different, wider in low-angle than in average- and high-angle individuals (p value = 0.000). High-angle individuals also had greater posttreatment external root resorption, even though the bony housing changed minimally. Conclusions Negative sequelae of orthodontic treatment are more frequently found in individuals with high mandibular plane angles and could be linked to their thin pre-existing alveolar housing.